Объединение решений в программном комплексе ANSYS 12 - Куликов, И. С.; Коваль, Ю. Г.; Томило, Е. В. (БНТУ, 2011)
Possibility on association of decisions in program complex ANSYS 12 on a problem example about mixing of liquids with various temperatures and speeds of movement in pipes is presented.